Finance needs of the agricultural midstream and the prospects for digital financial services - Ambler, Kate; de Brauw, Alan; Herskowitz, Sylvan; Pulido, Cristhian (International Food Policy Research Institute, 2022)
Recent literature suggests that agricultural value chains are changing rapidly and places an increasing focus on the importance of actors and activities taking place in the “midstream” of these value chains, after production and prior to final sale. This article discusses the financial needs of midstream actors in agricultural value chains, emphasizing differences across midstream activities and highlighting how value chain characteristics can influence both financial needs and potential remedies. The paper concludes with a discussion of the prospects of digital financial services to alleviate financial needs of midstream actors.